Edukasi Pencegahan Penyakit Demam berdarah Dengue dan Optimalisasi Pemanfaatan Tanaman Berpotensi Penolak Vektor Penular DBD - Yunus, Reni; Supiati, Supiati; Nurtimasiah, Wa Ode (Jurnal Inovasi, Pemberdayaan dan Pengabdian Masyarakat, 2024)
There are approximately 50 million cases of dengue fever every year, and 40% of the population is at risk of being infected with the dengue virus. Apart from utilizing government programs through the 3M program, dengue prevention measures can be taken by sowing larvicide. However, the use of chemical larvicides has disadvantages, such as repeated use of chemical larvicides carries the risk of contamination of pesticide residues in water, especially drinking water, and repeated use results in the emergence of resistance from various mosquito species. Research on plants with the potential to be larvicidal and repellent or mosquito repellents has proven that plants can be used as mosquito repellents, therefore it can eliminate the population level of the Aedes mosquito as a vector for transmitting dengue fever. The results of the research require to be introduced to the community,because indirectly reduce the occurrence of dengue fever cases in a village. The aim of this community service is to provide education to the public regarding Dengue Hemorrhagic Fever and information about plants that have the potential to repel mosquitoes as an effort to eliminate vectors that transmit dengue fever. This community service also aims to measure community knowledge about dengue hemorrhagic fever and its prevention. Educational activities regarding dengue hemorrhagic fever, prevention methods and socialization of plants that have the potential to repel dengue vectors were carried out on September 14 2023 in Taipa village, Lembo district, North Konawe district. In the education provided, it was seen that the participants were very active in asking questions about things they did not understand. The percentage increase in public knowledge regarding Dengue Hemorrhagic Fever after being given education was 76%.